The pattern of amyloid deposition in the lung - Looi, L.M. (1999)
A review of routine histopathological samples and autopsies examined at the Department of Pathology, University of Malaya revealed 15 cases of amyloidosis of the lung. Two were localized depositions limited to the lung while in the remainder, lung involvement was part of the picture of systemic amyloidosis. Both cases of localized amyloidosis presented with symptomatic lung/bronchial masses and a clinical diagnosis of tumour. Histology revealed "amyloidomas" associated with heavy plasma cell and lymphocytic infiltration and the presence of multinucleated giant cells.In both cases, the amyloid deposits were immunopositive for lambda light chains and negative for kappa chains and AA protein. One was a known systemic lupus erythematosus patient with polyclonal hypergammaglobulinaemia. The other patient was found to have plasma cell dyscrasia with monoclonal IgG lambda gammopathy. Both patients did not develop systemic amyloidosis. In contrast, lung involvement in systemic AA amyloidosis was not obvious clinically or macroscopically but was histologically evident in 75% of cases subjected to autopsy. Amyloid was detected mainly in the walls of arterioles and small vessels, and along the alveolar septa. It was less frequently detected in the pleura, along the basement membrane of the bronchial epithelium and around bronchial glands. In one case of systemic AL amyloidosis associated with multiple myeloma, an "amyloidoma" occurred in the subpleural region reminiscent of localized amyloidosis. These cases pose questions on (1) whether localized "tumour-like" amyloidosis is a forme fruste of systemic AL amyloidosis and (2) the differing pattern of tissue deposition of different chemical types of amyloid fibrils, with the suggestion that light chain amyloid has a greater tendency to nodular deposition than AA amyloid.